Anisotropic friction sliding rule influence on the mechanical systems dynamics - Wijata, Adam; Stańczyk, Bartosz; Awrejcewicz, Jan (Wydawnictwo Politechniki Łódzkiej, 2021)
Anisotropic friction can produce friction force which is not collinear with a sliding direction. How much friction deviates from a sliding direction is described with a so-called sliding potential or equivalently a sliding rule. A sliding potential is often described with an ellipse or a superellipse. In this paper we propose an oval curve which provides piecewise continuous mathematical description for a sliding rule and fits better to the experimental results than a typical superepllipse. For an exemplary mechanical system it is shown, that an anisotropic sliding potential can lead to an unstable equilibrium position in the system. Furthermore, for what parameters the unstable equilibrium occurs differs between sliding potential models. We have tested four different geometrical models of sliding potential in this regard.
Keywords: anisotropic friction; sliding potential; unstable equilibrium; tarcie anizotropowe; potencjał ślizgowy; równowaga niestabilna